2016
DOI: 10.1007/s11524-016-0052-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of Direct and Indirect Violence Exposure on Externalizing Behavior in Children

Abstract: The objective of this study was to examine the association between externalizing behaviors and indirect violence exposure, assessed both within the household and at the community level, as well as the interaction effect of indirect and direct violence exposure. A sample of parents of children ages 4-15 who have not been referred or enrolled in child welfare (n = 82) were recruited from the greater New Orleans community. Externalizing behavior was assessed with the Child Behavior Checklist (CBCL). The child's i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 83 publications
2
23
0
2
Order By: Relevance
“…Polyvictimization was highly prevalent in the present sample, as most of the children experienced three or more discrete types of maltreatment exposure, consistent with other high-risk samples (Lau et al, 2005; Manly et al, 2001). Externalizing problems were of clinical concern for the majority of this sample (57.3%), in line with prior research that maltreated children often exhibit elevated externalizing problems (Fleckman et al, 2016). Contrary to our first hypothesis, the final model indicated that polyvictimization and externalizing problems were marginally, but not significantly, related.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Polyvictimization was highly prevalent in the present sample, as most of the children experienced three or more discrete types of maltreatment exposure, consistent with other high-risk samples (Lau et al, 2005; Manly et al, 2001). Externalizing problems were of clinical concern for the majority of this sample (57.3%), in line with prior research that maltreated children often exhibit elevated externalizing problems (Fleckman et al, 2016). Contrary to our first hypothesis, the final model indicated that polyvictimization and externalizing problems were marginally, but not significantly, related.…”
Section: Discussionsupporting
confidence: 88%
“…Several mediators and moderators underlying this relationship have been identified, such as emotion regulation (Kim & Cicchetti, 2010), parenting styles (Lansford et al, 2006), and compromised attention (Roman, Ensor, & Hughes, 2016). A study of community children aged 4–15 years found that externalizing problems significantly increased for each additional adverse event exposure (Fleckman, Drury, Taylor, & Theall, 2016). Few studies have investigated the risk of externalizing behavior in the context of polyvictimization; it is essential to further delineate the complex relationship between co-occurring victimizations and externalizing symptomatology.…”
Section: Polyvictimization and Externalizing Behaviormentioning
confidence: 99%
“…In a study of African American adolescents from economically disadvantaged communities, 95% of youth endorsed exposures to more than one violent event, 30% reported hearing gunshots in the community, 65% had seen someone being threatened by a weapon, and 54% reported that someone close to them was shot or attacked [8]. In a recent cross-sectional study of younger children (aged 5–15 years) from the New Orleans area, all children reported physical aggression, and over one third (35%) reported witnessing community violence or had seen a friend or family member get hurt or mistreated [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a 2-year longitudinal study conducted by Weist, Acosta, and Youngstrom [30], researchers administered the Exposure to Violence Screening Measure to urban youths, examining prior exposures to violence (robbery, assaults, shootings, stabbings) and found that exposure increased with age. Numerous researchers [4, 10, 19, 40, 41] have discussed how desensitization impacts the way youth generally react to experiences and adaptive mechanisms to continuous violence exposure and develop adaptive mechanisms to continuous violence exposure that may downplay the self-reported symptoms of mental distress [42].…”
Section: Introductionmentioning
confidence: 99%
“…Both boys and girls experience violence in childhood but differ in the nature of the violence experienced (Landers, 2013;UNICEF, 2014). Violence experienced in childhood can be direct -when a child experiences aggression -or indirect, when she or he witnesses the aggression (Fleckman, Drury, Taylor, & Theall, 2016). Direct violence includes both interpersonal violence and self-directed violence (Krug, Mercy, Dahlberg, & Zwi, 2002).…”
Section: Introductionmentioning
confidence: 99%